The development of a policy framework for integrating smart asset management within operating theatres in a private healthcare group to mitigate critical system failure - Nel, Charles Benjamin Hirschowitz (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.